An internet based virtual reality intervention for preventing posttraumatic stress disorder - Freedman, Sara A.; Dayan, Ehud; Eitan, Renana (Frontiers in Virtual Reality, 2022)
Introduction: Research examining the prevention of Posttraumatic Stress Disorder (PTSD) has shown that selective treatments to those with high symptom levels, using trauma focused CBT are relatively successful in reducing symptoms and preventing chronic PTSD. However, uptake of these early treatments is often low. This study aimed to provide an internet based Virtual Reality treatment to overcome some of these barriers to early treatment. Method: The study received IRB approval from Hadassah Hospital (HMO 0056-013); its ClinicalTrials.gov identifier is NCT01760213. Recent survivors of motor vehicle accidents (N=1500) were assessed by telephone and online questionnaires. Patients meeting study criteria were randomly assigned to a Virtual Reality internet-based trauma-focused cognitive behavioral therapy (CBT) or waitlist control. Results: the majority of subjects recruited did not meet study criteria or were unwilling to participate. 14 subjects were randomly assigned to treatment or waitlist control. Results indicate that both groups show a decline in PTSD symptoms at follow up, with no significant differences between groups. Discussion: prevention of PTSD is a challenging goal, and internet-based interventions may play a role in this. The current study was not able to recruit sufficient participants to draw conclusions regarding the efficacy of the treatment. Proving services via the internet may not reduce barriers to care in this population